Zakat As An Alternative Revenue and Financing Resources for The State - Fathonih, Ahmad (al-'adalah, 2019)
Zakat is one of the religious obligations that have social, economic, political, and legal dimensions. The obligation has been effectively practiced by Muslims since the 7th century during the time of the Prophet Muhammad. The amount of zakat in Indonesia is very potential, reaching 217 trillion rupiahs, which can be used to solve the problem of poverty and socio-economic imbalances. Unfortunately, up to now the potential of zakat has not been able to reduce poverty and improve social welfare. The Zakat Management Act Number 23 of 2011 and Number 14 of 2014 concerning the Implementation of the Zakat Management Law only regulates the management of zakat under the supervision of the government. The government can manage zakat productively as a source of state income (non-tax state income) and state funding sources (State Sukuk or State Sharia Securities). This study finds that the difficulties faced by the Indonesian government to manage zakat funds productively are mostly related to people’s understanding of zakat as a religious obligation and not as a state obligation. Besides, zakat is mostly used for consumptive and unproductive purposes only.